Prevalence Of Suspected Beta Thalassemia Minor Based On Screening With Mentzer Index And Red Distribtion Width In Students Of Smp Negeri 7 Pujut - Prameswari, Larasita; Silvana Sari, Linda; Arum Lestarini, Ima (Jurnal Kedokteran, 2020)
Background : Beta thalassemia is blood disorder that it often found in Indonesia with high frequency of beta thalassemia carrier genes around 3 to 10%. Thalassemia has not been cured, but can be prevented by screening of thalassemia to identify individuals with beta minor thalassemia in population. The purpose of this study was to determine prevalence of anemia and prevalence of suspected beta thalassemia minor in students of SMP Negeri 7 Pujut based on Mentzer index and Red Distribution Width index. Methode: This study was an quantitative descriptive design with cross sectional approach. Total number of 130 students of SMP Negeri 7 Pujut were recruited with proportional random sampling stratified technique. Screening of beta thalassemia minor by calculating erythrocyte index of anemia blood samples using Mentzer index and Red Distribution Width index. Mentzer index was calculated by dividing Mean Corpuscular Volume (MCV) by Red Blood Count (RBC). RDW index was calculated by by multiplying MCV by RDW and divided by RBC. Result: According to data analysis, prevalence of anemia in students was 16.9% based on Hb concentrations for diagnosis anaemia based on WHO. Prevalence of suspected beta thalassemia minor was 0% based on Mentzer index and 4,6% based on RDW index. Conclusion: Prevalence of anemia in students was 16.9% based on Hb concentrations for diagnosis of anaemia WHO and prevalence of suspected beta thalassemia minor was 4,6% based on RDW index.